The Invisible Slavs Župa Bled in the "Prehistoric" Early Middle Ages - Pleterski, Andrej (Opera Instituti Archaeologici Sloveniae, 2013)
Is the inside-view into the life of people invisible to the written records possible, then? One cannot simple transfer oneself into the past and observe. However, one can immerse in the same landscape and seek for the residuals of the past in language, place names, folklore, ordering of the landscape and various material remains, or even in younger written records in the form of the so called wirkungsgeschichte (record of younger consequence of an earlier phenomenon). The least one achieves is the role of the passive observer. It is the aim of this book to go even further and to demonstrate that the "inside" perspective is not unattainable~it can be achieved by using a combination of various sources: written sources, archaeology, ethnology, philology and historic geography. The image of early medieval society in the Bled micro-region thus forming reveals the community with tightly economic and political ties. Weather or not it was referred to as Župa Bled is not confirmed by the written sources but it is at least likely.